COMMUNITY EMPOWERMENT IN MANAGING DAIRY MILK INTO A SUPERIOR PRODUCT - Tiara Juliana Jaya (Jurnal Abdi Masyarakat Multidisiplin, 2022)
The empowerment of dairy farmers in Indonesia has not been able to meet the needs of national milk demand. The research conducted is an effort to increase milk productivity. Each region has superior products that are expected to be able to become a foundation for the welfare of the community. One of the superior products of kradinan village is dairy cow's milk. With the existence of KKN DR UIN Malang, it is hoped that it will be able to provide assistance and community empowerment. The research method used is a qualitative descriptive approach. Data collection techniques include interviews, observations, documents, and focus group discussions and are refined by data triangulation. The results of KKM DR UIN Malang provide socialization of community utilization in creating superior products.